The distinguishing features of Indian outward FDI - O. A. Maltseva (Vestnik MGIMO-Universiteta)
This article analyses the outstanding features of Indian outward foreign direct investments, factors, which determine this process. Also this article examines the particularities of Indian transnational corporations’ behavior.